HCV: The Journey from Discovery to a Cure Volume I - Sofia, Michael J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Hepatitis C is a liver disease caused by the hepatitis C virus (HCV) and infects approximately 75 million individuals worldwide. It is also one of the major causes of liver cancer and liver transplants. The elucidation of the HCV genome, and the development of a whole cell system to study the virus spurred the search for novel direct acting antiviral drugs to cure this disease. This global effort culminated in the development of direct acting antiviral drugs that led to cure rates approaching 100% in all patient populations after only 8-12 weeks of therapy. These efforts resulted in one of the greatest achievements in public health and provides the potential for eliminating HCV as a major disease worldwide. This volume is aimed at a broad audience of academic and industrial scientists interested in the discovery and development of drugs to treat viral diseases and those interested in reading about one of the most unique accomplishments in biomedical research. The volume will provide a one of a kind reference work that highlights the many efforts, from the discovery of the HCV virus, to the invention of breakthrough medicines and their use in the real world to cure patients. It is the companion book to the volume "HCV: The Journey from Discovery to a Cure - Volume II".
Identification of the virus, the medical need and clearing the blood supply -- Mapping the HCV genome -- The molecular virology of HCV -- The development of the HCV replicon system -- The Evolution of IFN therapy for HCV -- Evolution of HCV NS5B Non-Nucleoside Inhibitors -- Evolution of HCV NS5B Nucleoside & Nucleotide Inhibitors -- Discovery and Development of Sofosbuvir -- Discovery of Beclabuvir -- Discovery of Dasabuvir -- Evolution of HCV NS3/4 protease inhibitors -- Discovery and Development of Telaprevir -- Discovery and Development of Boceprevir -- Discovery and Development of Asunaprevir.-Discovery and Development of Grazoprevir -- Discovery and Development of Simeprevir -- Discovery and Development of Paritaprevir & Glecaprevir.
Keywords: Medicinal chemistry; Virology; Clinical biochemistry; Bioorganic chemistry; Pharmaceutical chemistry; Medicinal Chemistry; Virology; Medical Biochemistry; Bioorganic Chemistry; Pharmaceutics